Determination of hyperregeneratory esophagopathy in dogs with clinical signs attributable to esophageal disease Bestimmung der hyperregeneratorischen Ösophago - pathie bei Hunden mit klinischen Anzeichen einer Speiseröhrenerkrankung - Münster, M.; Kook, P.; Araujo, R.; Hörauf, A.; Vieth, M. (Tieraerztliche Praxis Ausgabe Kleintiere Heimtiere, 2015)
Objective: It was hypothesized that typical characteristics of hyper-regeneratory esophagopathy (HRE) in humans such as basal cell hyperplasia and elongation of stromal papillae are also histologically detectable in canine esophageal epithelium, and that these changes are associated with clinical signs and endoscopic findings suggesting gastro - esophageal reflux (GER). Material and methods: Sixty-five adult dogs with clinical signs attributable to esophageal disease underwent esophagoscopy and biopsy. Clinical signs suggesting GER (regurgitation, ptyalism, painful discomfort) were prospectively evaluated through a questionnaire. Endoscopic mucosal alterations suggesting GER such as minimal endoscopic changes and obvious mucosal defects were assessed via video endoscopy. Biopsy specimens obtained from the esophageal squamous epithelium were evaluated histologically. The squamous epithelium's substructures of esophageal biopsies were quantitatively assessed through microscopic morphometry. Results: Esophageal squamous epithelium was considered normal in 48 dogs, and HRE was detected histologically in 17 dogs; both pathognomonic changes (basal cell hyperplasia, elongation of stromal papillae) were consistently present. Morphometrically assessed stromal papillary length and basal cell layer thickness was significantly (each, p < 0.0001) higher in the 17 dogs with HRE than in the 48 dogs without HRE, respectively. Overall, clinical signs suggesting GER were significantly (p = 0.02) more frequently encountered and regurgitation was significantly (p = 0.009) more common in the 17 dogs with HRE than in the 48 dogs without HRE. Similarly, endoscopic changes were significantly (p = 0.002) more frequently observed and minimal endoscopic changes suggesting GER were significantly (p = 0.004) more common in 17 dogs with HRE than in the 48 dogs without HRE. Conclusion and clinical relevance: Typical characteristics of hyperregeneratory esophagopathy in humans are also histologically detectable in canine esophageal epithelium. Histological changes are associated with clinical signs and endoscopic findings suggesting GER.
CRIS-Team Scopus Importer:2025-03-05